Pertimbangan Hakim dalam Menjatuhkan Pidana di Bawah Ancaman Minimum Khusus Terhadap Pelaku Tindak Pidana Pencabulan Anak. (Studi Kasus Putusan Pengadilan Negeri Payakumbuh Nomor 120/Pid.Sus/2022) - Kusuma Wardani, Khofifah; Ismansyah, Ismansyah; Zurnetti, Aria (Universitas Ekasakti, 2023)
The norms of judge's consideration are regulated juridically in Article 183 of the Criminal Procedure Code, which states that a judge, when imposing a crime on a defendant, may not impose the crime unless there are at least two valid pieces of evidence, so that the judge has confidence that a crime actually occurred and the defendant is guilty of doing it. The case that often occurs is child molestation as regulated in Article 81 of Law Number 35 of 2014 concerning Child Protection. The purpose of legal regulations regarding child molestation is to protect child victims from perpetrators of these crimes. In its application, discrepancies were found between written legal rules and those applied by judges. Another case of child molestation that occurred and that the author examined was in Payakumbuh, case number 120/Pid.Sus/2022/PN. This is quite unfortunate with the existence of SEMA Number 1 of 2017, because ultimately it is not SEMA that clarifies or provides guidance to Judges, but rather disrupts the legal order and tries to create new norms in the midst of existing norms. The conclusions (1) The judge's considerations from the